Development of 2D La(OH)3 /graphene nanohybrid by a facile solvothermal reduction process for high-performance supercapacitors. (10th August 2018) - Subasri, A.; Balakrishnan, K.; Nagarajan, E.R.; Devadoss, V.; Subramania, A.
Abstract: Nanostructured hybrids have attracted great interest in the development of high-performance supercapacitors. Herein, a novel hierarchical nanohybrid of La(OH)3 electrostatically anchored onto 2D-Graphene nanosheets (GNs) were prepared by a simple solvothermal reduction method and investigated as an electrode material for supercapacitors for the first time. This 2D La(OH)3 -G nanohybrid electrode exhibits a specific capacitance of 485 F g −1 at 1 A g −1 and 295 F g −1 at 15 A g −1 with 61% of capacitance retention from 1 A g −1 to 15 A g −1 in 6 M KOH in the potential window of −0.2–0.4 V. This nanohybrid electrode provides a convenient and advantageous way for charge and ion transport and highly accessible electroactive sites to improve the performance of supercapacitors. The asymmetric supercapacitor assembled with La(OH)3 -G nanohybrids as a positive electrode and activated carbon as negative electrode produce the highest specific capacitance of 69 F g −1 at of 1 A g −1 and retains 82.6% up to 5000 cycles with 97% Coulombic efficiency in 6 M KOH. These electrochemical findings demonstrate La(OH)3 -G nanohybrid as a potential candidate for supercapacitor applications. Graphical abstract: Image 1 Highlights: La(OH)3 -G nanohybrid is prepared by the solvothermal reduction process. La(OH)3 nanorods are electrostatically anchored onto GNs to form La(OH)3 -G nanohybrid. La(OH)3 -G electrode delivers a specific capacitance of 485 F g −1 . La(OH)3 /G.||AC delivers high specific capacitance of 69 F g −1 at 1 A g −1 with an energy density of 26 W h kg -1 .